Pengaruh Kompetensi Guru Terhadap Produktivitas Sekolah Pada Sekolah Dasar Islam Terpadu Di Kecamatan Klari Karawang - Sri Haryati Dewi; Nitta Kanya; Fajar Eryanto Septiawan (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The school productivity of each institution needs to be considered in order to create optimal graduate results. School productivity needs to be considered because it affects the growth and development of the institution. Therefore, this study was conducted where in the observation there were problems, especially at the Integrated Islamic Elementary School in Klari District, Karawang. The research method used is descriptive method and verification method. Population of 240 teachers, sample of 150 teachers, Non Probability sampling technique, based on sample provisions by Slovin, data collection technique questionnaire "Likert scale" and data processing technique path analysis and using SPSS version 25 application. Teacher competency variables can be stated in the category of good enough and running optimally, organizational culture variables can be stated in the category of good enough and so is the motivation variable is in the category of good enough and has an effect on school productivity in integrated Islamic elementary schools in Klari District, Karawang. Teacher competency, organizational culture and motivation have a significant relationship. Teacher competency on school productivity also has a greater influence. This study aims to determine how much influence teacher competence have on school productivity at the Integrated Islamic Elementary School in Klari District, Karawang. This study was conducted at the Integrated Islamic Elementary School in Klari District, Karawang.